Preparation method of gasification furnace slag-based zeolite molecular sieve loaded with nanoscale zero-valent iron and nickel
By loading nano zero-valent iron-nickel onto the gasification slag-based zeolite molecular sieve and using alkali solution treatment method, the problems of low utilization rate of gasification slag and high cost of synthesis of zeolites are solved, and the high-value utilization of gasification slag and high-efficiency effect of heavy metal adsorption is achieved.
Patent Information
- Application Number
- CN202311387971.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-25
AI Technical Summary
The prior art is difficult to effectively utilize gasification slag, and the cost of synthesizing zeolites is high. How to reduce the cost of synthesizing zeolites and improve the comprehensive utilization rate of gasification slag.
By loading nano zero-valent iron-nickel onto the gasification slag-based zeolite molecular sieve, and using alkali solution treatment method, molecular sieve products of different quality are obtained, achieving lower cost and higher comprehensive utilization rate of raw materials.
The high-value utilization of gasification slag is achieved, and a cost-effective heavy metal adsorption material is provided, which can effectively remove heavy metals from water, and is suitable for the treatment of domestic sewage, industrial wastewater and soil groundwater.
Smart Images

Figure CN119869444A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive utilization of gasification furnace slag, and in particular relates to a method for preparing a gasification furnace slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel. Background Art
[0002] With the development of industry, heavy metals are widely used in all walks of life, and their pollution has received increasing attention. Heavy metals have the characteristics of high solubility, strong mobility, and high toxicity, and cannot be purified by physical, chemical or biological methods in nature itself. Common heavy metal treatment methods include adsorption, chemical precipitation and biomineralization. Among them, adsorption is highly valued due to its economy and high efficiency. Common adsorption materials include biomass, lime, activated carbon, zeolite, etc.
[0003] my country is a country that uses coal as its main primary energy source. While coal gasification is widely used as a clean coal technology, it also produces a large amount of slag. According to statistics, the gasification slag produced by coal gasification technology exceeds 3.3×107t / a. The disposal of gasification slag is mainly piled up and landfilled, which not only occupies a large amount of arable land, but also contains a certain amount of heavy metals. Long-term dissolution can lead to the migration of heavy metals and cause pollution to soil and groundwater.
[0004] At present, only about 20% of gasification slag has been comprehensively utilized, and it is mainly used as low-end building materials. Acosta et al. added 50% clay to gasification slag with low carbon content (loss on ignition = 2.64%) to produce building bricks that meet the use requirements. Liu Kaiping et al. used gasification furnace coarse slag to replace natural sand as concrete fine aggregate, and the strength of the prepared concrete was higher than that of standard concrete. When the addition of gasification slag was 20%, the density of the wall material prepared by Yun Zheng et al. was less than 14.5g / cm3, and the compressive strength was higher than 30Mpa. In addition, Liu et al. used KOH as an activator and used gasification slag after flotation to prepare activated carbon with a specific surface area of 1226.8m2 / g. These applications are mainly laboratory research, and large-scale applications are relatively rare. Therefore, the high-value engineering utilization of gasification slag needs to be studied urgently.
[0005] Zeolite is a cage-like aluminum silicate mineral with a light gray or flesh-red color. Its structural skeleton is formed by a [TO4] tetrahedron (T is Si, Al) sharing an oxygen atom at the top. The cage-like porous structure of zeolite makes it widely used in fields such as water treatment and gas adsorption. At present, natural zeolite has gradually failed to meet market demand. At the same time, the adsorption performance and ion exchange capacity of natural zeolite are increasingly difficult to meet the requirements of industrial applications. Therefore, artificial synthesis of zeolite has become an important development direction. However, industrial synthesis of zeolite mainly uses chemical reagents as raw materials, and the preparation cost is relatively high. How to reduce its synthesis cost is an urgent problem to be solved. The synthesis of zeolite using fly ash from power plants has been studied for a long time. Gasification slag has a similar chemical composition to fly ash. Therefore, the synthesis of zeolite using gasification slag as raw material can not only solve the environmental problems caused by gasification slag, but also reduce the cost of raw materials for synthetic zeolite.
[0006] In the past decade, nano-zero-valent iron (nZVI) has been widely used in the treatment of various pollutants in aqueous solutions due to its strong reducing activity, high activity, non-toxicity, and low price. ZVI with nano-scale particle size exhibits outstanding activity due to its large surface area. In addition, nZVI has been shown to have excellent performance in removing heavy metals from wastewater by reduction, adsorption, and coprecipitation. However, nano-zero-valent iron is very easy to agglomerate and oxidize, resulting in reduced activity. Loading nano-zero-valent iron on zeolite molecular sieves can not only avoid nano-zero-valent iron agglomeration, but also facilitate recovery, thereby improving the activity and reuse rate of zeolite molecular sieves.
[0007] Therefore, the present application loads nano zero-valent iron-nickel bimetallic materials onto gasification furnace slag-based zeolite materials to obtain economical and efficient heavy metal adsorption materials. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a gasification slag-based zeolite molecular sieve loaded with nano zero-valent iron-nickel. By treating with an alkaline solution, molecular sieve products of different qualities can be obtained by grading, which has the effects of lower cost and higher comprehensive utilization rate of raw materials.
[0009] The technical solutions adopted are:
[0010] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, the method comprising the following steps:
[0011] (1) Mixing gasification slag and hydrochloric acid and stirring thoroughly;
[0012] (2) filtering, washing with deionized water to clean the hydrochloric acid, and then drying the filter residue; the hydrochloric acid filtrate after filtration can be collected and reused;
[0013] (3) adding NaOH solution to the filter residue obtained in step (2) and stirring;
[0014] (4) filtering the mixture after stirring in step (3), collecting the filtrate, and washing the obtained filter residue with deionized water and drying it to directly obtain the zeolite / C mixture A';
[0015] (5) adding CTAB solution to the filtrate obtained in step (4) and stirring, and adjusting the pH to acidic with sulfuric acid;
[0016] (6) filtering the liquid from step (5) to obtain a filter cake, washing and drying it, and then calcining it in a muffle furnace to obtain a zeolite molecular sieve B';
[0017] (7) dispersing the zeolite molecular sieves A' and B' obtained in step (4) and step (6) into an aqueous solution of ethanol respectively, and slowly adding an aqueous solution of ferric nitrate and nickel nitrate into the solution, stirring thoroughly, and then adding a NaBH4 solution and stirring;
[0018] (8) The suspensions obtained in step (7) are filtered, washed, and then vacuum dried to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0019] As a further preference, the gasification slag is dried overnight at 105° C. in a drying oven before use, and then ground with a ball mill to a size larger than 100 mesh.
[0020] The gasification slag contains 20-45% SiO2, 10-25% CaO, 8-15% Al2O3, 5-15% Fe2O3 and 3-37% residual carbon by weight.
[0021] As a further preference, the concentration of hydrochloric acid is 2-4 mol / L, and the usage ratio of gasification slag to hydrochloric acid is (1:5-20) g / mL.
[0022] As a further preference, the usage ratio of gasification slag to hydrochloric acid is (1:10-15) g / mL.
[0023] As a further preference, in the step (3), the concentration of the NaOH solution is 1.5 mol / L to 4 mol / L, and the stirring time is 0.5 h to 4 h.
[0024] Preferably, the concentration of the NaOH solution is 2 to 3 mol / L, and the stirring time is 1 to 2 h.
[0025] As a further preference, in the step (4), the filter residue is dried at 70-100° C. for 4-10 hours. Preferably, the filter residue is dried at 80-90° C. for 6-8 hours.
[0026] As a further preference, in the step (5), the concentration of the CTAB solution is 1-3 g CTAB / 100 mL water, and the solution is stirred at 20-50° C. for 1-4 h.
[0027] As a further preference, in the step (5), the pH of the solution after adjustment with sulfuric acid is 5 to 6.5.
[0028] Preferably, the concentration of the CTAB solution is 1.5-2 g CTAB / 100 mL water, and the solution is stirred at 30-40° C. for 2-3 h, and the pH of the solution after adjustment with sulfuric acid is 5-6.
[0029] As a further preference, in the step (6), the calcination temperature in the muffle furnace is 450-550° C., and the calcination time is 3-5 hours.
[0030] Preferably, the calcination temperature in the muffle furnace is 550° C. and the calcination time is 5 h.
[0031] As a further preference, in step (7), the ratio of zeolite molecular sieve to ethanol solution is 5 to 15 g zeolite molecular sieve / 100 mL ethanol solution.
[0032] Preferably, the ratio of zeolite molecular sieve to ethanol solution is 7-10 g zeolite molecular sieve / 100 mL ethanol solution.
[0033] Preferably, the concentration of the ethanol solution is 60 to 80%, more preferably 70 to 75%.
[0034] As a further preference, in the step (7), the mass ratio of the ethanol solution, the zeolite molecular sieve, and the iron and nickel is 15-25:5-15:0.3-1.
[0035] Preferably, the mass ratio of the ethanol solution, the zeolite molecular sieve, and the iron and nickel is 18-22: 8-10: 0.5-0.8.
[0036] As a further preference, in step (7), the concentration of the NaBH4 solution is 0.5 to 1 mol / L, and the addition rate is 2 to 6 mL / min.
[0037] Preferably, the concentration of the NaBH4 solution is 0.7-0.9 mol / L, and the addition rate is 3-5 mL / min.
[0038] As a further preference, the ratio of the volume of the added NaBH4 solution to the ethanol mixed aqueous solution of the zeolite molecular sieve, iron nitrate and nickel nitrate is 1:2.
[0039] As a further preference, in the step (8), the obtained suspension is filtered and washed three times with ethanol aqueous solution, and then vacuum dried at 50-80°C for 10-24h.
[0040] Preferably, the drying is carried out at 60-70° C. for 12-18 hours.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention uses gasification slag as raw material to prepare zeolite molecular sieve materials loaded with zero-valent bimetallic iron and nickel. On the one hand, it can realize the high-value utilization of gasification slag. On the other hand, the prepared material has a good treatment effect on heavy metals in water and can be used for the removal of heavy metals in domestic sewage, industrial wastewater and soil and groundwater.
[0043] The present invention adopts a NaOH solution excitation method, which is different from the traditional alkali fusion-hydrothermal synthesis method. It has lower cost and can fully utilize the high carbon content in the gasification slag. Zeolite / C porous materials and zeolite molecular sieves are obtained in batches, and then zero-valent bimetallic iron-nickel is loaded, which can avoid the agglomeration of zero-valent iron, have a smaller pore size and a larger specific surface area, and improve the activity and reuse rate of the zeolite molecular sieve. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The present invention is a flow chart of a method for preparing a gasification furnace slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel. DETAILED DESCRIPTION
[0045] The drawings are only used for illustrative purposes; for those skilled in the art, some well-known structures and their descriptions in the drawings may be omitted, and therefore, they should not be understood as limitations on the present invention.
[0046] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described in detail below in conjunction with embodiments and drawings.
[0047] Example 1
[0048] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel. In this embodiment, the gasification slag contains 40% SiO2, 10% CaO, 15% Al2O3, 15% Fe2O3 and 20% residual carbon by weight.
[0049] The specific implementation steps of the gasification furnace slag-based zeolite molecular sieve loaded with nano zero-valent iron and nickel are as follows:
[0050] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the gasification slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0051] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0052] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0053] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture, which is referred to as zeolite / C mixture A′;
[0054] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0055] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve, which was designated as mesoporous zeolite molecular sieve B′.
[0056] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0057] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0058] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 1.
[0059] Example 2
[0060] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0061] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 2 mol / L hydrochloric acid and stirred for 1 h.
[0062] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0063] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0064] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0065] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0066] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0067] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0068] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0069] Other unmentioned places are the same as those in Example 1.
[0070] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 1.
[0071] Example 3
[0072] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0073] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 4 mol / L hydrochloric acid and stirred for 1 h.
[0074] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0075] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0076] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0077] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0078] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0079] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0080] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0081] Other unmentioned places are the same as those in Example 1.
[0082] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 1.
[0083] Examples 1-3 were prepared using hydrochloric acid of different concentrations, and the performance test results of the obtained zeolite molecular sieve products loaded with zero-valent iron-nickel bimetallic were compared. The results are shown in Table 1.
[0084] Table 1 shows the specific surface area and Cu content of the products obtained in Examples 1-3. 2+ Comparison
[0085]
[0086] As shown in Table 1, the optimal hydrochloric acid concentration is 3 mol / L, at which point products A and B have higher specific surface area and adsorption capacity of Cu 2+ ability.
[0087] Example 4
[0088] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0089] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0090] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0091] (3) adding 1.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0092] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0093] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0094] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0095] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0096] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0097] Other unmentioned places are the same as those in Example 1.
[0098] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 2.
[0099] Example 5
[0100] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0101] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0102] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0103] (3) adding 3.0 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0104] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0105] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0106] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0107] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0108] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0109] Other unmentioned places are the same as those in Example 1.
[0110] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 2.
[0111] Example 6
[0112] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0113] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0114] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0115] (3) adding 4.0 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0116] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0117] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0118] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0119] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0120] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0121] Other unmentioned places are the same as those in Example 1.
[0122] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 2.
[0123] In Examples 1, 4, 5 and 6, different concentrations of NaOH solutions were used in step (3), and the performance test results of the obtained zeolite molecular sieve products loaded with zero-valent iron-nickel bimetallic were compared. The results are shown in Table 2.
[0124] Table 2 shows the specific surface area and Cu content of the products obtained in the examples. 2+ Comparison
[0125]
[0126] As shown in Table 2, the optimal NaOH concentration is 2.5-3 mol / L, at which time products A and B have higher specific surface area and adsorption capacity of Cu 2+ ability.
[0127] Example 7
[0128] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0129] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0130] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0131] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0132] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0133] (5) adding 50 mL of CTAB solution having a concentration of 1.0 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0134] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0135] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0136] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0137] Other unmentioned places are the same as those in Example 1.
[0138] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 3.
[0139] Example 8
[0140] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0141] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0142] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0143] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0144] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0145] (5) adding 50 mL of CTAB solution having a concentration of 2.4 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0146] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0147] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0148] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0149] Other unmentioned places are the same as those in Example 1.
[0150] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 3.
[0151] Example 9
[0152] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0153] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0154] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0155] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0156] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0157] (5) adding 50 mL of CTAB solution having a concentration of 3.0 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0158] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0159] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0160] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0161] Other unmentioned places are the same as those in Example 1.
[0162] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 3.
[0163] Example 10
[0164] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0165] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0166] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0167] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0168] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0169] (5) adding 50 mL of CTAB solution having a concentration of 1.5 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0170] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0171] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0172] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0173] Other unmentioned places are the same as those in Example 1.
[0174] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 3.
[0175] In Examples 1 and 7-10, CTAB solutions of different concentrations were used in step (5), and the performance test results of the obtained zeolite molecular sieve products loaded with zero-valent iron-nickel bimetallic were compared. The results are shown in Table 3.
[0176] Table 3 shows the specific surface area and product Cu obtained in Examples 1-3 2+ Comparison
[0177]
[0178] As shown in Table 3, the optimal CTAB concentration is 1.5-1.8 mol / L. At this time, products A and B have higher specific surface area and adsorption capacity of Cu 2+ ability.
[0179] Embodiment 11
[0180] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0181] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0182] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0183] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0184] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0185] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0186] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0187] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 4.80 g and 0.03 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0188] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0189] Other unmentioned places are the same as those in Example 1.
[0190] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 4.
[0191] Example 12
[0192] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0193] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0194] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0195] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0196] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0197] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0198] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0199] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 14.4 g and 0.09 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0200] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0201] Other unmentioned places are the same as those in Example 1.
[0202] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 4.
[0203] In Examples 1, 11 and 12, different amounts of ferric nitrate and nickel nitrate were added for preparation, and the performance test results of the obtained zeolite molecular sieve products loaded with zero-valent iron-nickel bimetallic were compared. The results are shown in Table 4.
[0204] Table 4 shows the specific surface area and Cu content of the products obtained in the examples. 2+ Comparison
[0205]
[0206] As shown in Table 4, the optimal concentrations of iron nitrate and nickel nitrate are 9.6 and 0.06 g / 50 mL ethanol aqueous solution. At this time, products A and B have high specific surface area and adsorption capacity of Cu 2+ ability.
[0207] Embodiment 13
[0208] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0209] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0210] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0211] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0212] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0213] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0214] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0215] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.9 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0216] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0217] Other unmentioned places are the same as those in Example 1.
[0218] The obtained zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 5.
[0219] Embodiment 14
[0220] A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, wherein the specific implementation steps of the method are as follows:
[0221] (1) After the gasification slag is dried, it is ball-milled at 300 r / min for 5 min. After passing through a 100-mesh sieve, 10 g of the slag is mixed with 100 mL of 3 mol / L hydrochloric acid and stirred for 1 h.
[0222] (2) Filter and rinse with deionized water to clean the hydrochloric acid until no Cl- is detected; then dry the filter residue at 80°C for 12 hours, and collect the hydrochloric acid filtrate after filtration and reuse it;
[0223] (3) adding 2.5 mol / L NaOH solution to the filter residue obtained after drying in step (2) and stirring for 1 h;
[0224] (4) filtering the mixture in step (3), washing the obtained filter cake thoroughly and drying it at 85° C. for 6 h to obtain a zeolite / C mixture A′;
[0225] (5) adding 50 mL of CTAB solution having a concentration of 1.8 g CTAB / 100 mL aqueous solution to the filtrate obtained in step (4), stirring the mixture at 35° C. for 2 h, and adjusting the pH to 5.5 with sulfuric acid;
[0226] (6) The liquid was filtered to obtain a filter cake, which was washed and dried at 85° C. for 6 h, and then calcined in a muffle furnace at 550° C. for 5 h to obtain a mesoporous zeolite molecular sieve B′.
[0227] (7) 4 g of the zeolite molecular sieve obtained in step (4) and step (6) and 50 mL of a 70% ethanol solution were added to a three-necked flask, and after ultrasonic dispersion for 30 min, 50 mL of an ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, with the addition amounts of iron nitrate and nickel nitrate being 9.60 g and 0.06 g, respectively. The mixture was stirred for 30 min, and then 300 mL of a 0.7 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred;
[0228] (8) The suspensions obtained in step (7) were filtered, washed three times with ethanol solution, and then vacuum dried at 70° C. for 12 h to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
[0229] Other unmentioned places are the same as those in Example 1.
[0230] The obtained zeolite sub-sieve product loaded with zero-valent iron-nickel bimetallic was subjected to performance testing, and the results are shown in Table 5.
[0231] Comparative Example 1
[0232] Take 5g of gasification slag and 6.5g of sodium hydroxide particles and mix them evenly in a crucible, and roast them at a certain alkali melting temperature for 90min. After cooling, weigh a certain mass of the roasted product and add 25mL of 2.0mol / L sodium hydroxide solution. After stirring evenly, continue to add 50mL of 1mol / L sodium aluminate solution, crystallize at 100℃ for 8h. After the reaction is completed, take out the product and filter it, wash the filter cake with water until it is neutral, and dry it at 80℃ for 2h to obtain zeolite molecular sieve product A.
[0233] Then, 4 g of zeolite molecular sieve and 50 mL of 70% ethanol solution were added to a three-necked flask. After ultrasonic dispersion for 30 minutes, 50 mL of ethanol aqueous solution of iron nitrate and nickel nitrate were slowly added, and the addition amounts of iron nitrate and nickel nitrate were 9.60 g and 0.06 g respectively. Stirring was carried out for 30 minutes, and then 300 mL of 0.8 mol / L NaBH4 solution was added at a rate of 4 mL / min and stirred; the obtained suspension was filtered, then washed with ethanol solution 3 times, and then vacuum dried at 70°C for 12 hours to obtain a zeolite molecular sieve product loaded with zero-valent iron-nickel bimetallic.
[0234] The products obtained in Examples 1, 13, and 14 were compared with the products obtained in Comparative Example 1. NaBH4 solutions of different concentrations were selected in Examples 1, 13, and 14, respectively. The comparative example was prepared by a traditional alkali fusion-hydrothermal treatment method. The performance comparison of the obtained products is shown in Table 5.
[0235] Table 5 shows the specific surface area and Cu content of the products obtained in the examples and comparative examples. 2+ Comparison
[0236]
[0237] As shown in Table 5, the optimal NaBH4 concentration is 0.8 mol / L. At this time, products A and B have higher specific surface area and adsorption capacity of Cu 2+ The alkaline solution excitation method can achieve graded utilization of gasification slag compared to the traditional alkaline melting-hydrothermal method, and the hollow zeolite molecular sieve product has a higher specific surface area.
[0238] The English abbreviations used in the present invention are:
[0239] CTAB-cetyltrimethylammonium bromide;
[0240] A', B', A, B only refer to the products of a certain stage and do not represent the actual product names.
[0241] The above-mentioned embodiments do not represent all the embodiments of the present invention. The present invention only lists some embodiments to illustrate the technical solutions.
[0242] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron and nickel, characterized in that: The method comprises the following steps: (1) Mixing gasification slag and hydrochloric acid and stirring thoroughly; (2) filtering, washing with deionized water to remove the hydrochloric acid, and then drying the filter residue; (3) adding NaOH solution to the filter residue obtained in step (2) and stirring; (4) filtering the mixture after stirring in step (3), collecting the filtrate, and washing the obtained filter residue with deionized water and drying it to directly obtain the zeolite / C mixture A'; (5) adding CTAB solution to the filtrate obtained in step (4) and stirring, and adjusting the pH to acidic with sulfuric acid; (6) filtering the liquid from step (5) to obtain a filter cake, washing and drying it, and then calcining it in a muffle furnace to obtain a zeolite molecular sieve B'; (7) dispersing the zeolite molecular sieves A' and B' obtained in step (4) and step (6) into an aqueous solution of ethanol respectively, and slowly adding an aqueous solution of ferric nitrate and nickel nitrate into the solution, stirring thoroughly, and then adding a NaBH4 solution and stirring; (8) The suspensions obtained in step (7) are filtered, washed, and then vacuum dried to obtain zeolite molecular sieve products A and B loaded with zero-valent iron-nickel bimetallic.
2. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 1, characterized in that: Before use, the gasification slag was dried overnight at 105° C. in a drying oven and then ground with a ball mill to a size larger than 100 meshes.
3. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (1), the concentration of hydrochloric acid is 2-4 mol / L, and the usage ratio of gasification slag to hydrochloric acid is (1:5-20) g / mL.
4. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 3, characterized in that: The usage ratio of gasification slag to hydrochloric acid is (1:10-15) g / mL.
5. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (3), the concentration of the NaOH solution is 1.5 to 4 mol / L, and the stirring is performed for 0.5 to 4 hours.
6. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (4), the filter residue is dried at 70-100° C. for 4-10 hours.
7. The method for preparing a gasification furnace slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (5), the concentration of the CTAB solution is 1-3 g CTAB / 100 mL water, and the solution is stirred at 20-50° C. for 1-4 h, and the pH value of the solution is 5-6.
5.
8. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (5), the pH of the solution after adjustment with sulfuric acid is 5 to 6.
5.
9. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (6), the calcination temperature in the muffle furnace is 450-550° C., and the calcination time is 3-5 hours.
10. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (7), the ratio of the zeolite molecular sieve to the ethanol solution is 5 to 15 g of zeolite molecular sieve / 100 mL.
11. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (7), the mass ratio of the ethanol solution, the zeolite molecular sieve, the iron and the nickel is 15-25:5-15:0.3-1.
12. The method for preparing a gasification slag-based zeolite molecular sieve loaded with nanometer zero-valent iron-nickel according to claim 2, characterized in that: In the step (7), the concentration of the NaBH4 solution is 0.5 to 1 mol / L, the addition rate is 2 to 6 mL / min, and the ratio of the added volume to the ethanol mixed aqueous solution of the zeolite molecular sieve, iron nitrate and nickel nitrate is 1:2.
Citation Information
Patent Citations
Permeable reaction wall active material and preparation method thereof
CN107473321A
Preparation method and application of Fe-Cu binary oxide adsorbent for removing antimony
CN108295804A
Preparation method and application of blast furnace ferronickel slag-based zeolite molecular sieve
CN112058219A
Modified zeolite filter material for treating phosphorus-containing industrial discharge water and preparation method thereof
CN112191223A
Permeable and adsorptive ceramic purifying block and preparing method thereof
KR1020110126350A